A systematic review of the impact of therapeutical biophilic design on health and wellbeing of patients and care providers in healthcare services settings - Al Khatib, Inas; Samara, Fatin; Ndiaye, Malick (Frontiers in Built Environment, 2024)
Hospitals often evoke negative feelings due to their antiseptic architecture and personal memories. Biophilic hospital design can reduce stress and enhance health and wellness for patients and caregivers, creating sustainable therapeutic environments. This research paper explores these environments and presents case studies demonstrating the positive outcomes of biophilic design on health and wellbeing. This paper systematically reviews and critically assesses literature using secondary data from peer-reviewed journals and reliable sources on sustainable design from 2010–2023. The results show that biophilic design in hospitals reduces hospitalization time, patient mortality, pain levels, and stress for healthcare providers. It alleviates anxiety, improves experiences for patients, families, and staff, reduces patient harm, and supports faster recovery. Overall, it positively influences the psychological and physiological responses of patients and staff. Future research should analyze the impact of individual biophilic design elements separately and explore implementation challenges. It should also quantify benefits such as reduced staff absenteeism and increased productivity. This study fills the gap of the limitation of holistic studies on biophilic design’s impact on patient care and service delivery in hospital settings.